Fashion and modular design – Modularity as a design strategy for sustainability - Daria Casciani (Agathón)
Fashion occupies an essential place in today’s society not only because of the production of garments and their impact at the end of their life but also because of the economic, cultural and social dynamics it determines. Modular design is a valuable strategy for creating complex systems from configurable, separable and adaptable modules that can influence sustainability. Through the review of scientific literature integrated with case studies from the professional world, this paper categorises current implementations of modular fashion design, highlighting the system architecture and describing opportunities and limitations regarding environmental, economic, cultural and social sustainability. From the analysis emerges the need for a multidisciplinary investigation of the topic through the study of new business models and Industry 4.0 technologies employing a design-led approach that deals with the design of products and services and consumption behaviour.